2008
DOI: 10.1121/1.2935095
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic pulse propagation in a bonded three-layered structure

Abstract: Bonded layers are used in the assembly of many critical functional parts of industrial equipment. In this work, ultrasonic pulse propagation in a steel-rubber-rubber bonded composite structure is investigated by means of computer simulation and pulse echo experimental evaluation. Ultrasonic pulse propagation is modelled using a 2D time domain finite-difference software. For the experimental measurements, two test samples were fabricated by bonding a thin layer of steel and two thin layers of rubber, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It was found that with the increase in high-temperature aging time, the ultrasonic longitudinal wave velocity of propellant grain generally showed an upward trend and the attenuation coefficient generally showed a downward trend [5] . At present, the application of composite solid propellant with ultrasonic nondestructive testing technology is still focused on the study of the bonding interface between shell and charge [6][7][8] . At the same time, the research on the performance state of composite solid propellant mostly adopts the method of mechanical property test.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that with the increase in high-temperature aging time, the ultrasonic longitudinal wave velocity of propellant grain generally showed an upward trend and the attenuation coefficient generally showed a downward trend [5] . At present, the application of composite solid propellant with ultrasonic nondestructive testing technology is still focused on the study of the bonding interface between shell and charge [6][7][8] . At the same time, the research on the performance state of composite solid propellant mostly adopts the method of mechanical property test.…”
Section: Introductionmentioning
confidence: 99%